Coupled changes between ruminating thoughts and resting-state brain networks during the transition into adulthood - Marchitelli, Rocco; Paillère Martinot, Marie-Laure; Trouvé, Alain; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Brühl, Rüdiger; Nees, Frauke; et al. (Molecular psychiatry, 2024)
Perseverative negative thoughts, known as rumination, might arise from emotional challenges and preclude mental health when transitioning into adulthood. Due to its multifaceted nature, rumination can take several ruminative response styles, that diverge in manifestations, severity, and mental health outcomes. Still, prospective ruminative phenotypes remain elusive insofar. Longitudinal study designs are ideal for stratifying ruminative response styles, especially with resting-state functional MRI whose setup naturally elicits people’s ruminative traits. Here, we considered self-rated questionnaires on rumination and psychopathology, along with resting-state functional MRI data in 595 individuals assessed at age 18 and 22 from the IMAGEN cohort. We conducted independent component analysis to characterize eight single static resting-state functional networks in each subject and session and furthermore conducted a dynamic analysis, tackling the time variations of functional networks during the entire scanning time. We then investigated their longitudinal mediation role between changes in three ruminative response styles (reflective pondering, brooding, and depressive rumination) and changes in internalizing and co-morbid externalizing symptoms. Four static and two dynamic networks longitudinally differentiated these ruminative styles and showed complemental sensitivity to internalizing and co-morbid externalizing symptoms. Among these networks, the right frontoparietal network covaried with all ruminative styles but did not play any mediation role towards psychopathology. The default mode, the salience, and the limbic networks prospectively stratified these ruminative styles, suggesting that maladaptive ruminative styles are associated with altered corticolimbic function. For static measures, only the salience network played a longitudinal causal role between brooding rumination and internalizing symptoms. Dynamic measures highlighted the default-mode mediation role between the other ruminative styles and co-morbid externalizing symptoms. In conclusion, we identified the ruminative styles’ psychometric and neural outcome specificities, supporting their translation into applied research on young adult mental healthcare.
Online veröffentlicht: 2. Juli 2024
Gesehen am 18.11.2024
Mitglieder des IMAGEN consortium: Marie-Laure Paillère Martinot, Jean-Luc Martinot, Eric Artiges, Tobias Banaschewski, Sarah Hohmann,Nathalie Holz, Arun L. W. Bokde, Sylvane Desrivières, Herta Flor, Hugh Garavan, Penny Gowland, Andreas Heinz, Henrik Walter, Rüdiger Brühl, Frauke Nees, Dimitri Papadopoulos Orfanos, Tomáš Paus, Luise Poustka, Nilakshi Vaidya, Juliane H. Fröhner, Michael N. Smolka, Robert Whelan and Gunter Schumann